2019
DOI: 10.1016/j.addma.2019.05.024
|View full text |Cite
|
Sign up to set email alerts
|

Numerical simulations of the mesostructure formation in material extrusion additive manufacturing

Abstract: A computational fluid dynamics model is used to predict the mesostructure formed by the successive deposition of parallel strands in material extrusion additive manufacturing. The numerical model simulates the extrusion of the material onto the substrate. The model takes into account the effect of the presence of the previously extruded material on the shape of the subsequently deposited strands. The simulated mesostructures are compared to optical micrographs of the mesostructures of 3D-printed samples, and t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
75
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 61 publications
(75 citation statements)
references
References 48 publications
(59 reference statements)
0
75
0
Order By: Relevance
“…The normalised layer thickness and the nozzle diameter ratio are employed to quantify the computational model’s geometry. In contrast, the velocity ratio is used to parameterise the amount of extruded materials with reference to the printing speed [ 14 ]. Given that the numerical results presented in dimensionless forms for fixed values of , , and , the obtained data can be considered equally valid for other simulation cases with various printing speeds nozzle diameters.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The normalised layer thickness and the nozzle diameter ratio are employed to quantify the computational model’s geometry. In contrast, the velocity ratio is used to parameterise the amount of extruded materials with reference to the printing speed [ 14 ]. Given that the numerical results presented in dimensionless forms for fixed values of , , and , the obtained data can be considered equally valid for other simulation cases with various printing speeds nozzle diameters.…”
Section: Methodsmentioning
confidence: 99%
“…Comminal et al [ 19 ] investigated the effects of the layer thickness and the printing speed on the shape of the deposited strand using a 3D CFD model of the strand deposition (assuming a Newtonian fluid); this CFD model was then validated by experiments in [ 8 ]. Serdeczny et al [ 14 ] expanded their research further to model the successive deposition of parallel strands to predict the mesostructure formed. They also acquire information about the porosity, the surface roughness, and the inter-and intra-layer bond line densities of the mesostructures.…”
Section: Introductionmentioning
confidence: 99%
“…Porosity formation and strand morphology are critical issues in extrusion that affect the part performance and are under significant influence of both the layer thickness and the strand-to-stand distance. It was reported that a lower filament layer thickness and the strand-to-strand distance led to smaller porosity and larger inter- and intra-layer bond line densities [ 19 ].…”
Section: Additive Manufacturing Processesmentioning
confidence: 99%
“…Recently, other researchers have done much work to specifically explore the deposition process in FFF, through numerical simulation [ 14 , 15 , 16 , 17 ] and theoretical analysis [ 18 ]. They have explored the effects of the speed ratio [ 14 , 15 ], viscosity [ 15 ], viscoelasticity [ 16 ], deposition flows [ 17 ], and interlayer contact pressures [ 18 ] on the dimensions of the deposited strands for particular combinations of processing parameters. As indicated in [ 19 ], a simple method is needed to calculate the geometries of the deposited filament for FFF.…”
Section: Introductionmentioning
confidence: 99%